Inclusion and political participation in the age of post-democracy - Fontes, Paulo (2022)
In the last few decades, we have been witnessing the deflation of the ideal of participative democracy. If, on the one hand, we go back to the original formulations of the 1960 and 1970, we can observe that these indicated the need to expand the spaces of collective democratic management in everyday life, particularly in the workplace. But, on the other hand, the models of the following decades accepted the circumscription of democratic practices to the state. In a parallel movement, the critic to the representative institutions and the political passivity that they promote was set aside, in favor of a perception that the difference between participation and representation is practically annulled. With that, the radicalism of the criticism to the deficit of participation in liberal democracies is lost. In a context of postmodernity, in which the maladies of modernity have not been remedied, along with the widespread disinterest in public affairs, especially in the younger strata, it is urgent to revitalize dormant democracies, mostly in the Western world. It becomes pertinent, as an objective for our work, based on existing scientific knowledge, to imagine and conceptualize new forms of inclusion and social and political participation that may renew the democratic system.